Contribuições à aprendizagem da utilização de Textos de Divulgação Científica de Educação Ambiental no Ensino de Química - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This paper aims to present the contributions to the learning of the use of Environmental Education Scientific Dissemination Texts (TDC) in Chemistry Teaching. The work was prepared by a student of the Exact Sciences Course - Degree of the Federal University of Pampa, campus Caçapava do Sul / RS and was applied in a rural school in the city of Caçapava do Sul / RS. Based on the theoretical frameworks used in this research, the use of TDC as a resource in teaching and learning processes can have advantages in understanding scientific meanings, since TDCs generally use an updated language, making the text easy for the reader to understand. . The research is of a qualitative nature in which from the analysis of the data three categories of analysis emerged: (i) Potentialities of text interpretation in the work with TDC, (ii) Difficulties the scientific concept in the TDC and (iii) Strategies used in the work with TDC. It can be concluded that the use of TDC, once worked in conjunction with the obligatory Environmental Education theme, can help students to have a better perception about the scientific aspects involved in the environmental and daily life context and a better awareness with the environment. use of natural resources.
Keywords: Textos de Divulgação Científica; Educação Ambiental; Ensino de Química; Texts of Scientific Dissemination; Environmental Education; Chemistry Teaching; CNPQ::CIENCIAS EXATAS E DA TERRA